Phylogenetic analysis of forty Solanum melongena L. accessions by SDS-page - Umar, Aisha; Shah, Anis Ali; Khan, Muhammad Tajammal (Bangladesh Journal of Botany, 2020)
Work was carried out to resolve the existing intraspecific taxonomic relation and protein richest accessions of Solanum melongena by using SDS-PAGE with the reference of their genetic diversity. Phylogenetic relatedness within samples was studied by cluster analysis using an Unweighted Pair Group Method with Arithmetic Mean (UPGMA) to construct a dendrogram. Electrophoretogram of accessions No. (1-19) 018477, 018482 (Faisalabad), 18484 (Sahiwal), whereas accessions from 20 - 40 from D. I Khan (18504, 18500, 18505, 14466(3), Sahiwal (20344) and Batgram (20509) was unique in protein banding position. Largest dendrogram of cluster 1 divided into 6 (6a,b), 7 (7a,b), 8 (8a,b) and 9 (9a,b) sub clusters including accessions 20425 - 4745(3). The results demonstrated that accessions have low level of genetic diversity and almost similar protein contents. No relationship was found between genetic divergence and genetic status of the samples.